A novel metal-organic framework precursor strategy to fabricate sub-micron CuO microspheres for catalytic thermal decomposition of ammonium perchlorate. (March 2021) - Guo, Zhiliang; Zhang, Qingchun; Liu, Huiyu; Zhang, Hewen; Zhang, Jinhao; Zuo, Jin; Jin, Bo; Peng, Rufang
Highlights: A novel air-flow impacting (AFI) technique for MOFs precursor strategy synthesis was first reported. The precursor HKUST-1 microrods subsequently convert to CuO microspheres with a particle diameter about 1 μm. The MOF derived CuO microspheres remarkably improve the catalytic property in AP-based composite solid rocket propellants. Abstract: A novel metal-organic framework (MOF) precursor strategy to fabricate CuO microspheres via air-flow impacting (AFI) synthetic method was reprted in the work. The MOF precursor HKUST-1 and its derived CuO microspheres were characterized by means of X-ray diffraction (XRD) and scanning electron microscopy (SEM). In addition, the catalytic activity of CuO microspheres on the thermal decomposition of ammonium perchlorate (AP) was investigated by differential thermal analysis (DTA). The results of DTA indicated that the addition of CuO microspheres to AP observably reduces the decomposition temperature due to its high contact area and much catalytic active sites. The HKUST-1 derived CuO microspheres are expected to remarkably improve the catalytic performance in AP-based composite solid rocket propellants.